Models of global gene expression define major domains of cell type and tissue identity. Issue 5 (30th January 2017) - Hutchins, Andrew P.; Yang, Zhongzhou; Li, Yuhao; He, Fangfang; Fu, Xiuling; Wang, Xiaoshan; Li, Dongwei; Liu, Kairong; He, Jiangping; Wang, Yong; Chen, Jiekai; Esteban, Miguel A.; et al.
Abstract: The current classification of cells in an organism is largely based on their anatomic and developmental origin. Cells types and tissues are traditionally classified into those that arise from the three embryonic germ layers, the ectoderm, mesoderm and endoderm, but this model does not take into account the organization of cell type-specific patterns of gene expression. Here, we present computational models for cell type and tissue specification derived from a collection of 921 RNA-sequencing samples from 272 distinct mouse cell types or tissues. In an unbiased fashion, this analysis accurately predicts the three known germ layers. Unexpectedly, this analysis also suggests that in total there are eight major domains of cell type-specification, corresponding to the neurectoderm, neural crest, surface ectoderm, endoderm, mesoderm, blood mesoderm, germ cells and the embryonic domain. Further, we identify putative genes responsible for specifying the domain and the cell type. This model has implications for understanding trans-lineage differentiation for stem cells, developmental cell biology and regenerative medicine.